Fireproof coating as well as preparation method and application thereof
By using black phosphorus nanosheets to modify hollow glass microbeads in the fire-retardant coating, the problem of insufficient water resistance and adhesion of the existing fire-retardant coating is solved, and the flame retardant performance and fire-retardant duration of the coating are significantly improved.
Patent Information
- Application Number
- CN202411870512.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing fire-resistant coating has poor water resistance, and its adhesion becomes worse in environments with high humidity, which easily falls off, resulting in a reduced fire-proof effect.
The hollow glass microbeads are modified with black phosphorus nanosheets. The layered structure of black phosphorus and the mobility and thermal insulation of the hollow glass microbeads are used to significantly improve the flame retardant performance, water resistance and adhesion performance of the coating.
It significantly improves the flame retardant performance, water resistance and adhesion properties of the fire-resistant coating, extends the fire resistance duration of the coating, and ensures stability and fire resistance in high humidity environments.
Smart Images

Figure QLYQS_1 
Figure BDA0005195638370000011 
Figure BDA0005195638370000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of protective coatings, in particular to a fire retardant coating and a preparation method and application thereof. Background Art
[0002] Steel structures are widely used in the modern construction industry because of their light weight, high strength, large span, large space, good seismic performance, convenient hoisting construction and short construction time. As a non-combustible building material, steel's mechanical properties such as yield strength, tensile strength and elastic modulus decrease with increasing temperature under the high temperature of fire. When the temperature rises to about 500°C, its mechanical strength will decrease by 60%, bending and deformation will occur, and the bearing capacity will be lost, resulting in bending of steel columns and beams and collapse of buildings. In order to extend the bearing capacity of steel structures under high temperature of fire, it is most practical, simple and convenient to directly spray fire retardant coatings on steel components. The fireproof and heat-insulating performance of steel structure fire retardant coatings is good, the construction is not restricted by the geometric shape of the steel structure, generally no auxiliary facilities are required, and the coating is light in weight and has a certain aesthetic decorative effect. However, the existing fire retardant coatings have poor water resistance, and in an environment with high humidity, the adhesion to steel becomes poor. During the fire protection process, they are easy to fall off, which greatly reduces the fire prevention effect.
[0003] Therefore, it is necessary to provide a high-performance fire-retardant coating that is excellent in water resistance, adhesion, and flame retardancy and is environmentally friendly. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a high-performance fire retardant coating which is excellent in water resistance, adhesion, flame retardancy and environmental protection.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a fire retardant coating, comprising the following components in parts by weight based on 100 parts by weight:
[0007]
[0008]
[0009] In the fire retardant coating of the present invention, the black phosphorus nanosheet-modified hollow glass microspheres simultaneously utilize the layered structural characteristics of black phosphorus and the mobility and heat insulation of the hollow glass microspheres, which can significantly improve the flame retardancy, water resistance and adhesion to steel of the prepared coating.
[0010] Specifically: (1) Black phosphorus will not decompose until it is above 500°C. This high temperature stability provides the advantage of delayed thermal decomposition under fire conditions, allowing it to exert flame retardant effects for a longer period of time; after decomposition, black phosphorus will release products such as phosphoric anhydride, forming a fire-resistant isolation layer to prevent the spread of flames to the internal matrix; the two-dimensional layered structure of black phosphorus enhances the interfacial interaction with the polymer matrix, improves the overall structural strength of the coating, and avoids the reduction in mechanical properties caused by traditional flame retardants. (2) Due to its low density and light weight, hollow glass microspheres can move quickly in the matrix, driving the black phosphorus nanosheets on the surface to migrate to the surface of the coating, forming a protective layer with a certain density and strength, improving the crack resistance and water resistance of the coating surface. This protective layer can effectively prevent the decrease in adhesion to the steel substrate due to the penetration of water vapor.
[0011] In addition, the coating containing black phosphorus nanosheet-modified hollow glass microspheres can further reduce the melt viscosity of the substrate, making the construction of the fire-retardant coating smoother, improving the processing performance of the material, and ensuring the quality and construction convenience of the fire-retardant coating.
[0012] Preferably, in the black phosphorus nanosheet-modified hollow glass microspheres, the weight ratio of the black phosphorus nanosheets to the hollow glass microspheres is (0.005-0.02): 1. Within this usage ratio range, the black phosphorus nanosheets and the hollow glass microspheres can give full play to the high flame retardancy of black phosphorus and the migration performance of the hollow glass microspheres in the matrix, and significantly improve the flame retardancy, water resistance and adhesion performance of the prepared fire retardant coating to steel.
[0013] Preferably, the particle size D of the hollow glass microspheres is n50 10~40μm, D n50 It indicates the particle size corresponding to when the cumulative number of the hollow glass microspheres reaches 50%.
[0014] Preferably, the black phosphorus nanosheet-modified hollow glass microspheres include first black phosphorus nanosheet-modified hollow glass microspheres and second black phosphorus nanosheet-modified hollow glass microspheres, satisfying: D n50-A >D n50-B , D n50-A represents the particle size of the first black phosphorus nanosheet-modified hollow glass microspheres, in μm; D n50-B represents the particle size of the second black phosphorus nanosheet-modified hollow glass microspheres, in μm; the mass ratio of the first black phosphorus nanosheet-modified hollow glass microspheres to the second black phosphorus nanosheet-modified hollow glass microspheres is (1-1.5):1.
[0015] It should be noted that in the present invention, the surface of the hollow glass microspheres is modified by black phosphorus nanosheets. Since the particle size of the hollow glass microspheres is at the micron level, the particle size of the modifier black phosphorus nanosheets is at the nanometer level. Therefore, after the surface of the micron-level hollow glass microspheres is modified by nanometer-level black phosphorus nanosheets, the particle size of the hollow glass microspheres modified by the black phosphorus nanosheets is not affected. In the present invention, the particle size of the hollow glass microspheres modified by the black phosphorus nanosheets can be expressed by the particle size of the hollow glass microspheres.
[0016] Two sizes of hollow glass microspheres are added to the coating system. The hollow glass microspheres modified by black phosphorus nanosheets can form a specific dispersed network structure in the system by utilizing the different migration rates of hollow glass microspheres of different sizes in the coating system. This specific network structure has more excellent flame retardant properties. The first black phosphorus nanosheet-modified hollow glass microspheres (low density) with a relatively large particle size have good mobility in the coating. During the coating and curing film formation process, the surface-modified black phosphorus nanosheets can be driven to migrate to the coating surface to form a protective layer with a certain density and strength, thereby improving the crack resistance of the coating surface and increasing the fire resistance of the coating. The second black phosphorus nanosheet-modified hollow glass microspheres (higher density) with a relatively smaller particle size settle to the side close to the substrate during the coating process, which can improve the adhesion to the substrate and ensure that they will not fall off for a long time, thereby increasing the fire protection time.
[0017] In the present invention, the black phosphorus nanosheet-modified hollow glass microspheres are prepared according to a method comprising the following steps:
[0018] (1) dissolving black phosphorus nanosheets in a good solvent and dispersing them evenly in an inert atmosphere to obtain a brown dispersion 1;
[0019] (2) dissolving a silane coupling agent in a good solvent, adjusting the pH value of the system to 4-5, and after uniform dispersion, adding hollow glass microspheres, and after uniform dispersion, obtaining dispersion 2;
[0020] (3) After the dispersion 1 obtained in step (1) and the dispersion 2 obtained in step (2) are uniformly mixed, the temperature is raised to 40-60° C. for reaction for 30-60 min, and after filtering, the obtained solid product is dried to obtain the black phosphorus nanosheet-modified hollow glass microspheres.
[0021] Preferably, the good solvent in step (1) and step (2) is an ethanol-water solution with a mass fraction of 50-75 wt%.
[0022] Preferably, the inert atmosphere in step (1) is a gas atmosphere formed by at least one gas selected from the group consisting of helium, neon, argon and nitrogen.
[0023] Preferably, in the dispersion 1 in step (1), the mass concentration of black phosphorus nanosheets is 0.05-0.4%.
[0024] Preferably, in the dispersion 2 in step (2), the mass concentration of the silane coupling agent is 0.5-2%.
[0025] Preferably, the drying temperature in step (2) is 70-90° C., and the drying is performed to constant weight.
[0026] Preferably, the black phosphorus nanosheets are prepared from black phosphorus powder by mechanical grinding using red phosphorus as a precursor, and then oxidized black phosphorus (OBP) nanosheets are prepared by liquid phase exfoliation. The black phosphorus nanosheets prepared in this way have hydroxyl (-OH), carboxyl (-COOH) and carbonyl (-C=O-) groups on the surface, which can improve the adhesion to the steel surface.
[0027] Optionally, the silane coupling agent includes but is not limited to at least one of γ-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)trimethoxysilane, and 3-glycidoxypropyltrimethoxysilane.
[0028] Preferably, the polyvinyl acetate emulsion includes Emultex FR 797 and Emultex FR 728. Further preferably, the weight ratio of Emultex FR 797 to Emultex FR 728 is (0.8-1.2):1, and more preferably 1:1. The glass transition temperature of the two emulsions after compounding is low, so only a small amount of film-forming aids need to be added to the coating formula to form a film. Moreover, the two emulsions are environmentally friendly products and do not contain APEO and halogen.
[0029] In the present invention, ammonium polyphosphate, pentaerythritol and melamine are all flame retardant fillers. The addition of black phosphorus nanosheets modified hollow glass microspheres can work together with them. With the addition of a relatively small amount of flame retardant fillers, the flame retardant properties of the coating can be significantly improved. The addition of a relatively small amount of flame retardant fillers can further improve the mechanical strength of the coating. Moreover, the reduction in the amount of melamine used can further improve the environmental performance.
[0030] Preferably, the weight ratio of the ammonium polyphosphate, pentaerythritol and melamine is (2-3):1:1. The polymer n of the ammonium polyphosphate is preferably n>1000, and is prepared by type II crystal transformation, and the decomposition temperature is 212°C. The particle size of the pentaerythritol is less than 40μm, wherein the content of monopentaerythritol is about 87%, the content of dipentaerythritol is about 7%, the content of hydroxyl is about 48%-50%, and the decomposition temperature of the pentaerythritol is 280°C. The pentaerythritol with the above characteristics can be dehydrated into carbon under the action of the acid generated by the decomposition of ammonium polyphosphate, and finally form a good foaming layer. The decomposition temperature of melamine is greater than 280°C, the sublimation temperature is greater than 354°C, and it contains abundant gas sources. Therefore, the above-mentioned ammonium polyphosphate, pentaerythritol and melamine are compounded in the above mass ratios as a flame retardant system, which can make the expanded carbonaceous thermal insulation layer formed by the coating at high temperature dense and not easy to fall off, and the fireproof and thermal insulation effect is better.
[0031] Preferably, the reinforcing filler includes at least one of titanium dioxide, sepiolite and ceramic fiber.
[0032] Preferably, the titanium dioxide is rutile titanium dioxide, which can significantly improve the fire resistance limit of thin-coat steel structure fire retardant coatings, is easily dispersed in water, has good hiding power and high refractive index.
[0033] Preferably, the sepiolite has a particle size of less than 15 μm (greater than 800 mesh), contains hydrous magnesium-rich silicate clay minerals with a layered chain structure, and is in the form of a fibrous aggregate, and has the characteristics of light weight, heat insulation, radiation resistance and good thermal stability.
[0034] Preferably, the ceramic fiber has an average diameter of 4.5 μm, a glass transition temperature of 731° C., a softening point of 875° C., and a melting point of >1000° C. The ceramic fiber having the above characteristics has good toughness, thermal stability and chemical stability, low thermal conductivity, high temperature resistance, high strength, and uniform dispersion.
[0035] The titanium dioxide, sepiolite and ceramic fiber are compounded in the dosage of the formula of the present invention, which can significantly improve the fire resistance limit of the coating. The layered chain structure of sepiolite and the linear structure of ceramic fiber make the expanded carbon layer form a continuous solid phase skeleton, while the gas phase exists continuously in the skeleton gap of the fiber material. This special structure enables the carbon layer to withstand the impact of flames and airflow, thereby improving the medium- and long-term fireproof and heat-insulating effects.
[0036] Film-forming aids, wetting and dispersing agents, mildew-proofing agents, defoaming agents, pH regulators, and thickeners commonly used in the art can all be used in the present invention.
[0037] Optionally, the film-forming aid includes but is not limited to at least one of triethylene glycol ethyl ether, triethylene glycol monobutyl ether and tripropylene glycol monobutyl ether. The film-forming aid can reduce the lowest film-forming temperature of the emulsion, so that the emulsion can fuse and form a film at a lower temperature; after the film is formed, the film-forming aid will gradually evaporate, so that the mechanical properties and hardness of the coating film are restored to the original level.
[0038] Optionally, the wetting and dispersing agent includes but is not limited to at least one of fatty acid ethylene oxide adducts, polyethylene glycol-type polyols, and polyethyleneimide derivatives, all of which are non-ionic wetting and dispersing agents.
[0039] Optionally, the mildew preventer includes but is not limited to heat-resistant isothiazolinone mildew preventer.
[0040] Optionally, the defoaming agent includes but is not limited to polyether siloxane copolymer, which has good compatibility with aqueous polyvinyl acetate emulsion and good defoaming effect.
[0041] Optionally, the pH adjuster includes but is not limited to at least one of 2-amino-2methyl-1-propanol and dimethylethanolamine.
[0042] Optionally, the thickener includes but is not limited to an acrylic acid associative thickener, which has shear-thinning flow characteristics in a high solid content system.
[0043] The second aspect of the present invention provides a method for preparing the fire retardant coating according to the first aspect of the present invention, comprising the following steps:
[0044] The fire retardant coating is obtained by mixing and uniformly dispersing water, a wetting dispersant, a pH regulator, a defoamer, black phosphorus nanosheet-modified hollow glass microspheres, a reinforcing filler, a membrane aid, a polyvinyl acetate emulsion, pentaerythritol, ammonium polyphosphate, melamine, a mildew inhibitor, and a thickener.
[0045] Preferably, in order to further improve the dispersibility of each component in the fire retardant coating system, the method for preparing the fire retardant coating comprises the following steps:
[0046] (1) Mix water, wetting dispersant, pH adjuster and defoamer and disperse them evenly;
[0047] (2) adding black phosphorus nanosheet-modified hollow glass microspheres and reinforcing fillers into the dispersed system of step (1);
[0048] (3) adding a film-forming aid, polyvinyl acetate emulsion, pentaerythritol, ammonium polyphosphate and melamine to the dispersed system of step (2) and dispersing them uniformly;
[0049] (4) Add a mildew preventer and a thickener to the dispersion system of step (3) and disperse them evenly to obtain the fire retardant coating.
[0050] The third aspect of the present invention provides the use of the fire retardant coating described in the first aspect of the present invention. The fire retardant coating is applied to the surface of steel and cured to obtain a fire retardant coating.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The present invention adds black phosphorus nanosheets to the water-based polyvinyl acetate emulsion flame retardant fireproof coating, and utilizes the layered structure characteristics of black phosphorus and the mobility and heat insulation of the hollow glass microspheres, so as to significantly improve the flame retardant performance, water resistance and adhesion performance to steel of the prepared coating. DETAILED DESCRIPTION
[0053] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0054] The relevant raw materials and their sources used in the embodiments and comparative examples of the present invention are as follows:
[0055]
[0056]
[0057] The black phosphorus nanosheet-modified hollow glass microspheres are prepared by self-modification in the present invention, and the specific preparation method comprises the following steps:
[0058] (1) dissolving black phosphorus nanosheets in a 75 wt % ethanol-water solution, and uniformly dispersing the nanosheets by ultrasonication at room temperature (25±5° C.) in a nitrogen atmosphere to obtain a brown dispersion 1 with a concentration of 0.1 wt %;
[0059] (2) dissolving a silane coupling agent in a 75 wt % ethanol-water solution, wherein the concentration of the silane coupling agent γ-aminopropyltriethoxysilane in the solution is 1 wt %, adjusting the pH value of the solution to 4-5 using hydrochloric acid, and after ultrasonic dispersion, adding hollow glass microspheres, and further ultrasonic dispersion, obtaining dispersion 2;
[0060] (3) After the dispersion 1 obtained in step (1) and the dispersion 2 obtained in step (2) are uniformly mixed, the temperature is raised to 40-60° C. for reaction for 30-60 min, and after filtering, the obtained solid product is placed in an oven at 70-90° C. and dried to constant weight to obtain the black phosphorus nanosheet-modified hollow glass microspheres.
[0061] The black phosphorus nanosheets in the embodiment of the present invention are prepared from red phosphorus as a precursor, using a mechanical grinding method to prepare black phosphorus powder, and then using a liquid phase exfoliation method to prepare oxidized black phosphorus (OBP) nanosheets. The specific preparation method is:
[0062] (1) Place red phosphorus powder and zirconium oxide balls (ball-to-powder ratio 30:1) into a 80 cm 3 The ceramic container was sealed after being filled with argon gas, and mechanically ground for 58 hours at a speed of 1500r / min, and then the ceramic container was brought back to the glove box to store the black phosphorus powder;
[0063] (2) Using DMF as a solvent, ultrasonic liquid phase exfoliation of black phosphorus powder was performed at room temperature: first, black phosphorus powder and DMF (concentration of 1 mg / mL) were added to a centrifuge tube, and argon gas was injected into the centrifuge tube, which was then immediately sealed with polytetrafluoroethylene tape and paraffin film; during the room temperature ultrasonic process, the test tube was shaken once every hour to disperse the unexfoliated powder particles at the bottom into the solvent to improve the exfoliation efficiency. After 12 hours of ultrasonic exfoliation, the upper half of the dispersion was collected by centrifugation, and the exfoliated black phosphorus oxide nanosheets were collected by filtration.
[0064] By selecting hollow glass microspheres with different particle sizes and adjusting the dosage ratio of dispersion 1 and dispersion 2, a series of black phosphorus nanosheet-modified hollow glass microspheres can be prepared. The specific parameters are shown in Table 1:
[0065] Table 1 Black phosphorus nanosheets modified hollow glass microspheres
[0066]
[0067]
[0068] Examples 1-13
[0069] This embodiment provides a fire retardant coating, and the preparation method includes the following steps, according to the raw material formula in Table 2 and Table 3:
[0070] (1) Mix water, wetting dispersant, pH adjuster and defoamer and disperse them evenly;
[0071] (2) adding black phosphorus nanosheet-modified hollow glass microspheres and reinforcing fillers into the dispersed system of step (1);
[0072] (3) adding a film-forming aid, polyvinyl acetate emulsion, pentaerythritol, ammonium polyphosphate and melamine to the dispersed system of step (2) and dispersing them uniformly;
[0073] (4) Add a mildew preventer and a thickener to the dispersion system of step (3) and disperse them evenly to obtain the fire retardant coating.
[0074] Table 2
[0075]
[0076]
[0077] Table 3
[0078]
[0079] Comparative Example 1
[0080] A fire retardant coating is provided, which is prepared by referring to the method of Example 1. The difference from Example 1 is that the black phosphorus nanosheet-modified hollow glass microspheres are replaced by a mixture of black phosphorus nanosheets and hollow glass microspheres of equal weight, and no chemical modification is performed, but only physical mixing.
[0081] Comparative Example 2
[0082] A fire retardant coating is provided, which is prepared by referring to the method of Example 1. The difference from Example 1 is that in the black phosphorus nanosheet-modified hollow glass microspheres, the black phosphorus nanosheets are replaced by red phosphorus.
[0083] Comparative Example 3
[0084] A fire retardant coating is provided, which is prepared by referring to the method of Example 1. The difference from Example 1 is that, during the preparation of hollow glass microspheres modified with black phosphorus nanosheets, red phosphorus is mechanically ground to obtain black phosphorus powder, and then liquid phase exfoliation is not performed.
[0085] Comparative Example 4
[0086] A fire retardant coating is provided, which is prepared by referring to the method of Example 1, except that the black phosphorus nanosheet-modified hollow glass microspheres are replaced by position-modified hollow glass microspheres.
[0087] Performance Testing
[0088] The performance of the fire retardant coatings obtained in the above embodiments and comparative examples was characterized and tested in accordance with GB14907-2018. The test results are shown in Table 4.
[0089] Table 4-1
[0090]
[0091]
[0092] Table 4-2
[0093]
[0094]
[0095] From the above results we can see that:
[0096] The present invention adds black phosphorus nanosheets to the water-based polyvinyl acetate emulsion flame retardant fireproof coating, and utilizes the layered structure characteristics of black phosphorus and the mobility and heat insulation of the hollow glass microspheres, so as to significantly improve the flame retardant performance, water resistance and adhesion performance to steel of the prepared coating.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A fire retardant coating, characterized in that: Based on 100 parts by weight, the following components are included:
2. The fire retardant coating according to claim 1, characterized in that: In the black phosphorus nanosheet-modified hollow glass microspheres, the weight ratio of the black phosphorus nanosheets to the hollow glass microspheres is (0.005-0.02):
1.
3. The fire retardant coating according to claim 2, characterized in that: The particle size D of the hollow glass microspheres n50 10-40μm, D n50 It indicates the particle size corresponding to when the cumulative number of the hollow glass microspheres reaches 50%.
4. The fire retardant coating according to claim 1, characterized in that: The black phosphorus nanosheet-modified hollow glass microspheres include first black phosphorus nanosheet-modified hollow glass microspheres and second black phosphorus nanosheet-modified hollow glass microspheres; satisfying: D n50-A >D n50-B , D n50-A represents the particle size of the first black phosphorus nanosheet-modified hollow glass microspheres, in μm; D n50-B represents the particle size of the second black phosphorus nanosheet-modified hollow glass microspheres, in μm; The mass ratio of the first black phosphorus nanosheet-modified hollow glass microspheres to the second black phosphorus nanosheet-modified hollow glass microspheres is (1-1.5):
1.
5. The fire retardant coating according to claim 1, characterized in that: The reinforcing filler includes at least one of titanium dioxide, sepiolite and ceramic fiber.
6. The fire retardant coating according to claim 1, characterized in that: The film-forming aid includes at least one of triethylene glycol ethyl ether, triethylene glycol monobutyl ether and tripropylene glycol monobutyl ether.
7. The fire retardant coating according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The polyvinyl acetate emulsion includes Emultex FR 797 and Emultex FR 728; (2) The wetting and dispersing agent includes at least one of fatty acid ethylene oxide adducts, polyethylene glycol type polyols, and polyethylene imide derivatives; (3) The antifungal agent includes a heat-resistant isothiazolinone antifungal agent; (4) The defoaming agent comprises a polyether siloxane copolymer; (5) The pH adjuster includes at least one of 2-amino-2-methyl-1-propanol and dimethylethanolamine; (6) The thickener includes an acrylic acid associative thickener.
8. The fire retardant coating according to claim 1, characterized in that: The black phosphorus nanosheet-modified hollow glass microspheres are prepared according to a method comprising the following steps: (1) dissolving black phosphorus nanosheets in a good solvent and dispersing them evenly in an inert atmosphere to obtain a brown dispersion 1; (2) dissolving a silane coupling agent in a good solvent, adjusting the pH value of the system to 4-5, and after uniform dispersion, adding hollow glass microspheres, and after uniform dispersion, obtaining dispersion 2; (3) After the dispersion 1 obtained in step (1) and the dispersion 2 obtained in step (2) are uniformly mixed, the temperature is raised to 40-60° C. for reaction for 30-60 min, and after filtering, the obtained solid product is dried to obtain the black phosphorus nanosheet-modified hollow glass microspheres.
9. The method for preparing the fire retardant coating according to any one of claims 1 to 8, characterized in that: The steps include: The fire retardant coating is obtained by mixing and uniformly dispersing water, a wetting dispersant, a pH regulator, a defoamer, black phosphorus nanosheet-modified hollow glass microspheres, a reinforcing filler, a membrane aid, a polyvinyl acetate emulsion, pentaerythritol, ammonium polyphosphate, melamine, a mildew inhibitor, and a thickener. Add thin-layer black phosphorus nanosheet-modified hollow glass microspheres, titanium dioxide, sepiolite and ceramic fibers to the dispersion obtained in step (1) and disperse them evenly.
10. The use of the fire retardant coating according to any one of claims 1 to 8, characterized in that: The fireproof paint is applied to the surface of the steel material and is cured to obtain a fireproof coating.
Citation Information
Patent Citations
Fireproof paint
CN104774509A
Lightweight polymer nano-composite material with isolation structure, and preparation method thereof
CN110564159A
Preparation method and application of two-dimensional material nanosheet coated microspheres
CN110694559A
Water-based indoor intumescent fire-retardant coating for steel structure and preparation method thereof
CN112708316A
Anticorrosive and flame-retardant epoxy resin coating and preparation method thereof
CN113388308A